Radiosensitizing properties of dual-functionalized carbon nanostructures loaded with temozolomide - Milenkovska, Radmila; Geskovski, Nikola; Shalabalija, Dushko; Mihailova, Ljubica; Makreski, Petre; Lukarski, Dushko; Stojkovski, Igor; Simonoska Crcarevska, Maja; Mladenovska, Kristina (Beilstein Journal of Nanotechnology, 2025)
In the present study, temozolomide (TMZ), a drug used for the treatment of anaplastic astrocytoma and glioblastoma multiforme (GBM), was incorporated into multiwalled carbon nanotubes (MWCNTs) and a MWCNTs–graphene (MWCNTs-G) hybrid compound, covalently functionalized with polyethylene glycol (PEG) 6000 and folic acid (FA), with an aim to prepare nanocarriers with the potential to prolong the drug circulation time, cross the blood–brain–tumor barrier (BBTB), and provide targeted and controlled drug release in the brain tumor cells. Cytotoxicity and effects on cell membrane integrity of the blank and TMZ-loaded dual-functionalized carbon nanostructures (CNs) were evaluated in vitro on a GBM cell line (U87MG), as well as their radiosensitizing properties after exposure of the pre-treated GBM cells to gamma radiation with a standard clinical dose for patients with GBM. All prepared formulations underwent biopharmaceutical and physicochemical characterization, including the formulations exposed to irradiation under the same conditions. For physicochemical characterization of the formulations, different techniques were used by which successful functionalization of the CNs and TMZ loading were confirmed and visualized; no significant changes in the structure of the CNs and TMZ after irradiation were observed. With single and dual functionalization, formulations with relatively high TMZ loading efficiency and drug content were prepared. They exhibited homogeneous particle size distributions and mean particle sizes and surface charges suitable for crossing the BBTB and targeting brain cancer cells. A biphasic drug release profile was observed for all functionalized TMZ-loaded formulations in simulated in vivo conditions, with a sustained release pointing to the potential for controlled release of TMZ in brain tumor cells. The formulations of the hybrid CN MWCNTs-G compared to the corresponding MWCNTs were characterized by a similar or slightly higher TMZ content, larger particle size, similar surface charge, and slightly faster TMZ release, which can be attributed to the planar structure of graphene that promotes TMZ binding to the surface on a larger scale. For the irradiated CNs, lower values for particle size, more positive values for surface charge, and accelerated TMZ release were observed, which could be explained by changes in the physicochemical characteristics of the prepared formulations upon irradiation. Significant concentration-dependent toxicity was observed for blank dual-functionalized CNs, being higher for MWCNTs-G-PEG6000-FA compared to MWCNTs-PEG6000-FA at the same formulation concentrations. With incorporation of TMZ into the functionalized CNs, the cell viability additionally decreased, maintaining the trend for higher cytotoxicity of the hybrid CN. Additional decrease in the viability of cells was observed when GBM cells pre-treated with the corresponding CNs were exposed to irradiation, which could be ascribed to changes in size, surface charge, and release kinetics of TMZ and to irradiation-induced changes in the microenvironment and cell membranes that promote uptake of a larger volume of carriers in the GBM cells. The higher cytotoxicity observed in the hybrid carrier formulations could most likely be attributed to the length of the hybrid carrier and the higher proportion of planar surface, which promotes more intense contact with the cells and rupture of cell membranes. Overall, the findings demonstrate the radiosensitizing properties of not only TMZ but also of CNs and point to a clinical benefit from combined treatment with carbon nanocarriers of TMZ and radiotherapy in GBM.
Keywords: carbon nanostructures; cytotoxicity; glioblastoma multiforme; radiosensitizing properties; temozolomide